Student flows and migration: an empirical analysis - Axel Dreher; Panu Poutvaara (Institute for the Study of Labor (IZA), 2005)
Using panel data for 78 countries of origin we examine the impact of student flows to the United States on subsequent migration there over the period 1971-2001. What we find is that the stock of foreign students is an important predictor of subsequent migration. This holds true whether or not the lagged endogenous variable is included. The relationship is robust to the inclusion of time and country dummies, and remains when we account for outliers. The basic results also hold for a cross section of 36 countries of origin and 9 host countries. Our results have important policy implications which we discuss in the last section.
Keywords: 330; migration; education; student flows; brain drain; Studium; Studierende; Internationale Wanderung; Internationale Wanderung; Einwanderung; USA; Auslandsaufenthalt; Ausländisch